Recommendations, Experiences and Conclusions From Realized Aftercare Public Policies in Czech Republic - Jan Stejskal; Tana Karlikova (European Regional Science Association (ERSA), 2006)
Czech Republic has become one of leading destinations for production foreign investments in Europe in last ten years. This success has been influenced by several factors including history, geography, policy development, economic and social progress transformation and also from Czech Republic's entrance into NATO and the European Union. We must also take into account traditions, labour skills, price and labour productivity. The central and regional government initiatives (from municipalities and larger regions) can play active roles in foreign investment attraction. Local and central government agencies of western countries are sources of such new and direct investments to Czech Republic. Because of higher economic standards in these countries, they are able to invest internationally with greater ease and comfort. National entrepreneurs are also sources for economic development and new business. The goals of the public policies focused on the "aftercare" can be: - Support with development and expansion, - Assisting with problem solving during enterprise development, - Training and help with restructuring, - Support and assistance for multi-national corporations and investors with: research and development, design, setting up centres with a network of experts, mentors and shareable resources, - Support and assistance with networking (and advertising?), - Developing "clusters" which are centres concentrating on excellence within global competition and markets, - Many more. These specified activities can be realized with financial support from the Structural funds from the European budget and by current operating programmes already in place within the Czech Republic. This paper focuses on the research analysis interpretation of entrepreneur environment. This case study (or research) was held in Czech Republic in May 2005. We would like to make some recommendations (in the form of "best practises") to inspire other countries (which solve similar problems) and provide information. Attention will be given to defining recommendations and offering conclusions to the compatibility with the new "learning regions" theory.
Keywords: 330